Evaluation of Antiarthritic Potential of Methanolic Extract of Gentiana kurroo Royle. (6th November 2014) - Mubashir, Khan; Ganai, Bashir A.; Ghazanfar, Khalid; Akbar, Seema
Abstract : Rheumatoid arthritis is a systemic disorder which involves the activation of immune system against the self-tissues. The main targets of this disease are the joints. Being systemic the development of this disease involves different mechanisms and thus the exact cause of this disease remains unknown. Although different drugs have been developed, none has been found to be the cure for this disease. In the current study the rat carrageenin paw was used as a model for acute inflammation and mycobacterium induced adjuvant arthritic model was used for exploring the antiarthritic potential of methanolic extract of Gentiana kurroo . In this study the different extracts tested showed less inhibition of acute inflammation than methanolic extract. The methanolic extract was further used in different doses and the anti-inflammatory efficacy was found to be dose dependent. The results obtained were significant with the control and the standard groups. In the arthritic model the methanolic extract showed decrease in the paw volume of arthritic animals and also in the arthritic symptoms. Again the results obtained were found to be significantly dose dependent. From the results obtained it can be concluded that this extract may serve as a source of drug against the rheumatoid arthritis.